Controlled reduction of graphene oxide laminate and its applications for ultra-wideband microwave absorption. (30th April 2020) - Pan, Kewen; Leng, Ting; Song, Jun; Ji, Chengyu; Zhang, Jiawei; Li, Jiashen; Novoselov, Kostya S.; Hu, Zhirun
Abstract: In this work, we first screen print thin GO laminates on Kapton film and then chemically reduce to rGO with desired sheet resistance by controlling printing cycles and reduction time. The thin rGO laminates have a wide range of conductivity from 2.8 S m −1 up to 1.3 × 10 4 S m −1, exhibiting excellent consistency of electric performance even after 50000 times bending. Commonly used rGO reduction level characterization methods have been compared with the proposed sheet resistance method. It is revealed that the later has higher variation with reduction time, providing a new method for reduction monitoring of rGO. Benefiting from the tunability of its sheet resistance, the rGO laminate not only can be used in flexible electronic circuits as conductors or resistors, but also highly efficient to absorb microwave radiations with proper design. Therefore, a printed, three-layer, Jaumann structured microwave absorber has been designed, fabricated and characterised. The maximum microwave absorption rate is up to 99.9997% where the −10 dB fractional bandwidth is over 153%, which covers L, S and C bands. Moreover, the fabricated absorber can absorb efficiently even when the incident angle is as low as 20°. Full design procedure, simulation and measurement results are presented.